О Распределении пульсаров различных типов в галактике - Андреасян, Р. Р.; Андреасян, А. Р.; Паронян, Г. М.; Сукиасян, А. Г.
This work considers the spatial and period distributions of various types of pulsars. Based on the analysis of observational data for more than 3.800 pulsars, the following key results were obtained: The characteristic distance of normal radio pulsars from the Galactic plane increases with their characteristic age. Millisecond pulsars of all types - including those located in Galactic globular clusters, those emitting in the gamma-ray and X-ray ranges, and those in the Galactic field that emit only in the radio band - are found to be very old objects, with average characteristic ages of several billion years. These pulsars are distributed within a broad layer near the Galactic plane, with a characteristic distance σ of approximately 500 parsecs. A distinct group of GRS pulsars with relatively long periods significantly differs from normal radio pulsars. While the peak of the period distribution for normal radio pulsars lies around log(P0) = -0.3, the peak for GRS pulsars is shifted substantially to the left. These GRS pulsars are located in a thin layer close to the Galactic plane, with a characteristic distance σ of about 160 parsecs, and have an average age of roughly one hundred thousand years.
Keywords: Пульсары